Fully Integrated SiGe HBT BiCMOS Transmit-Receive Front-End IC for 5G mmW Radio with A Reconfigurable Built-In Diode RF Switch - Han, Insu; Lee, Hanjung; Ju, Inchan (Digest of Papers - IEEE Radio Frequency Integrated Circuits Symposium, 2024)
This work presents a novel SiGe HBT BiCMOS TRX front-end for 5G mmW radio. A built-in base-to-collector diode (DBC) of a CB HBT in a cascode, with a coupled line impedance inverting balun, is reconfigured to reverse- or forward-biased to act as a PA or an RF switch in TX and RX modes, respectively. This architecture enables to remove any lossy switch in TX path, which leads to improvement in Pout, PAE, and NF simultaneously. It attains peak Pout of 22.0 dBm, 36.5% PAE, and the minimum NF of 3.08 dB at 28 GHz. It also supports linear amplification of 400 MHz 64 QAM 5G NR FR2 CP signal.
Keywords: Balun; BiCMOS; Fifth-generation (5g); Front end; Front-end; HBT BiCMOS; Millimeter-wave; Millimeter-wave radio; Power amplifier; SiGe HBTs; Balun; BiCMOS; fifth-generation (5G); front-end (FE); HBT; millimeter-wave (mmW); power amplifier (PA); SiGe